Pemantauan kecepatan dan suhu engine dengan Teknologi Internet of Things (IoT) - Guswandri Guswandri; Khairul Amri; Nofriyandi R; Refnal Marzuki; Rino Sukma (AEEJ : Journal of Automotive Engineering and Vocational Education, 2023)
The use of technology has made human life easier, all sectors have merged with technology, such as Internet of Things (IoT) technology where an object is embedded with technology such as sensors and software with the aim of communicating with each other and exchanging data via software as long as it is still connected to the internet. This test aims to monitor engine speed and temperature. This research and testing uses a standard measuring instrument development method that uses a Tachometer to a measuring instrument with IoT technology that uses sensors. The design of the engine speed and temperature monitoring tool with Internet of Things technology uses several main tools, namely the Arduino Uno module, ESP8266, speed and temperature sensors which can be monitored using a smartphone. The results of engine speed monitoring by comparing standard measuring instruments with IoT technology monitoring tools or presentation of the average failure of the Tachometer and monitoring tools are 1.35. This means that the level of precision of monitoring tools with IoT technology is better than standard tools. Pemanfaatan teknologi telah mempermudah kehidupan manusia, semua sektor telah melebur bersama teknologi, seperti halnya teknologi Internet of things (IoT) dimana suatu objek ditanamkan teknologi seperti sensor dan software dengan tujuan saling berkomunikasi dan bertukar data melalui software selama masih terhubung ke internet. Pengujian ini bertujuan untuk memonitor kecepatan dan suhu engine. Penelitian dan pengujian ini menggunakan motode pengembangan alat ukur standar yang menggunakan Tachometer ke alat ukur dengan teknologi IoT yang menggunakan Sensor. Rancang bangun alat pemantauan kecepatan dan suhu engine dengan teknologi Internet of Things ini menggunakan beberapa alat utama yaitu Arduino uno modul, ESP8266, Sensor kecepatan dan suhu yang monitoringnya menggunakan Smartphone. Hasil pemantauan kecepatan engine dengan membandingkan antara alat ukur standar dengan alat pemantauan teknologi IoT atau presentasi rata-rata kegagalan Tachometer dan alat monitoring sebesar 1,35 . Artinya tingkat presisi alat pemantauan dengan tekno;ogi IoT ini lebih baik dari alat standar.